GROUP COUNSELING SERVICES EFFECTIVENESS IN REDUCING STUDENT BEHAVIOR AGGRESSIVE SMA 6 PADANGSIDIMPUAN STATE ACADEMIC YEAR 2015-2016 - Sukatno Sukatrno (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The problem in this research is still their students behave aggressively and due to the lack of guidance and counseling role in the school environment . In this research to reduce aggressive behavior of students researcher uses group counseling services . This study aims to (1) To find out how the effectiveness of group counseling services in reducing aggressive behavior of students before and after tutoring services group in the experimental group at SMAN 6 Padangsidimpuan School Year 2015-2016, (2) To find out how the effectiveness of group counseling services in reducing aggressive behavior of students before and after conventional services in the control group at SMAN 6 Padangsidimpuan Academic Year 2015- 2016. This type of research is True Experimental Design with shapes Pretest-Posttest Control Group Design. The study population class X SMAN 6 Padangsidimpuan totaling 6 class. The research sample X4 grade students as an experimental class of 10 students and class X5 as the control class of 10 students. As a data collection tool is questionnaire. Analysis of the data using the Wilcoxon Signed Rank Test by using SPSS version 20.00. On the results of the first hypothesis test score Z of -2.701b with Asymp.Sig (2-tailed) 0.005 ≤ 0.05. And the results of the second hypothesis test score Z for -2.601b with Asymp.Sig (2-tailed) 0.005 ≤ 0.05 so it can be concluded that the first and second hypothesis tested in this study can be accepted, because the statistical analysis there are significant differences in reducing aggressive behavior of students before and after treatment group counseling services. On average posttest experimental class of 142.8000 while posttest control class is 135.1000. There are significant differences in reducing aggressive behavior of students in the experimental class and control. Based on the above findings, can disimpilkan that there is a group counseling service effectiveness in reducing aggressive behavior of students in class X SMAN 6 Padangsidimpuan Academic Year 2015-2016.